2020
DOI: 10.3390/ijms21082938
|View full text |Cite
|
Sign up to set email alerts
|

Hemokinin-1 Gene Expression Is Upregulated in Trigeminal Ganglia in an Inflammatory Orofacial Pain Model: Potential Role in Peripheral Sensitization

Abstract: A large percentage of primary sensory neurons in the trigeminal ganglia (TG) contain neuropeptides such as tachykinins or calcitonin gene-related peptide. Neuropeptides released from the central terminals of primary afferents sensitize the secondary nociceptive neurons in the trigeminal nucleus caudalis (TNC), but also activate glial cells contributing to neuroinflammation and consequent sensitization in chronic orofacial pain and migraine. In the present study, we investigated the newest member of the tachyki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 108 publications
2
17
0
Order By: Relevance
“…These findings, as a whole, indicated that (i) the F residue in the "FXGLM" motif played a crucial role in the bioactivity of tachykinins in the fish model, and (ii) the Phe to Val mutation form in the "VXGLM" motif represented the molecular determinant in HK1 leading to weak agonistic actions on SLα regulation, presumably by interfering the interaction with target receptors. Our findings were also in agreement with the previous studies in mammalian cell models, e.g., COS-7 cells with NK3 receptor [9,12], confirming that the C-terminal "FXGLM" motif was essential for the bioactivity and receptor binding [32,50].…”
Section: Discussionsupporting
confidence: 92%
“…These findings, as a whole, indicated that (i) the F residue in the "FXGLM" motif played a crucial role in the bioactivity of tachykinins in the fish model, and (ii) the Phe to Val mutation form in the "VXGLM" motif represented the molecular determinant in HK1 leading to weak agonistic actions on SLα regulation, presumably by interfering the interaction with target receptors. Our findings were also in agreement with the previous studies in mammalian cell models, e.g., COS-7 cells with NK3 receptor [9,12], confirming that the C-terminal "FXGLM" motif was essential for the bioactivity and receptor binding [32,50].…”
Section: Discussionsupporting
confidence: 92%
“…Tissue samples were thawed out on ice and homogenized in TRI reagent. After homegenization, total RNA was extracted using Direct-zol RNA MicroPrep (Zymo Research) according to the manufacturer’s instructions ( Aczél et al, 2020 ). The quantity of the extracted RNA was examined using Nanodrop ND-1000 Spectrophotometer V3.5 (Nano-Drop Technologies, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…SensiFAST™ Probe Lo-ROX Kit (Meridiane Bioscience, Memphis, United States) was used according to the manual in the QuantStudio five Real-Time PCR System (Thermo Fisher Scientific). Transcripts of the reference gene glucuronidase beta ( Gusb , Kecskés et al, 2020 ) and the target gene Tac4 were evaluated using FAM-conjugated specific probes (Mm01197698_m1, and Mm00474083_m1 respectively, Thermo Fisher Scientific). The gene expression was calculated using ΔΔCt method ( Pfaffl, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genes coding for proteins in the tachykinin family have recently been examined in two separate studies. 57 , 58 Neurokinin 3 receptor and hemokinin-1 receptor, coded by Tacr3 and Tac4 respectively, are suggested to contribute to development of trigeminal neuropathic pain. Downregulation of Tacr3 worked protective against pain, while upregulation of Tac4 was seen after CFA-injection in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest that the downregulation plays a protective role in treating allodynia, by suppressing the hyperexcitability in neurons. Another study 58 observed upregulation of Tac4 gene, encoding Hemokinin-1 (HK-1), concluding that HK-1 participates in pain transmission in the trigeminal system by interacting between sensory neurons and satellite glial cells.…”
Section: Discussionmentioning
confidence: 99%